2021
DOI: 10.1007/s00330-021-07873-2
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative breast magnetic resonance imaging in patients with ductal carcinoma in situ: a systematic review for the European Commission Initiative on Breast Cancer (ECIBC)

Abstract: Objective To evaluate the impact of preoperative MRI in the management of Ductal carcinoma in situ (DCIS). Methods We searched the PubMed, EMBASE and Cochrane Library databases to identify randomised clinical trials (RCTs) or cohort studies assessing the impact of preoperative breast MRI in surgical outcomes, treatment change or loco-regional recurrence. We provided pooled estimates for odds ratios (OR), relative risks (RR) and proportions and assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…30,33 Still, the potential for surgical outcome improvements with MRI remains unclear. A meta-analysis 34 and systematic review 35 found limited evidence that MRI reduced reoperation rate, although many of the included studies predated published guidelines to improve quality of imaging acquisition 36 and interpretation. 37 The single-arm ECOG-ACRIN E4112 DCIS trial showed that when MRI is performed in accordance with American College of Radiology accreditation requirements, rate of successful WLE is high (96%) while re-excision (22%) is low.…”
mentioning
confidence: 99%
“…30,33 Still, the potential for surgical outcome improvements with MRI remains unclear. A meta-analysis 34 and systematic review 35 found limited evidence that MRI reduced reoperation rate, although many of the included studies predated published guidelines to improve quality of imaging acquisition 36 and interpretation. 37 The single-arm ECOG-ACRIN E4112 DCIS trial showed that when MRI is performed in accordance with American College of Radiology accreditation requirements, rate of successful WLE is high (96%) while re-excision (22%) is low.…”
mentioning
confidence: 99%
“…4 In addition, the findings of possible multicentric disease, whether confirmed with a biopsy or not, are associated with higher mastectomy rates [5][6][7] without a demonstrated improvement in surgical outcomes, cancer recurrence rates, or long-term survival. 8,9 Although a host of factors may play a role in a patient's surgical choice, data suggests that new information from preoperative MRI likely influences patients' decisionmaking regarding mastectomy. 10 The American Society of Breast Surgeons currently states mastectomy is indicated for any cancer unsuitable for breast conservation surgery (BCS) based on tumor size, multicentricity, insufficient response to neoadjuvant chemotherapy, and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI also provides high sensitivity, it is expensive, and there is conflicting evidence as to whether preoperative MRI is beneficial to DCIS patients (24)(25)(26)(27)(28). A recent systematic review by Canelo-Aybar et al (29) showed that preoperative MRI did not reduce the rate of repeat surgery or mastectomy. With increasing access to imaging technology and screening, patients with DCIS can be identified earlier.…”
Section: Introductionmentioning
confidence: 99%